Inconsistency in freedom of contract for banking dispute resolution in Indonesia - Suryadi, Suryadi; Marwa, Muhammad Habibi Miftakhul; Muhammadi, Fauzan; Zuliyah, Siti; Megawati , Megawati (Faculty of Law, University of Muhammadiyah Malang, 2024)
This research interprets the manner and existence of contradictions in POJK No. 61/POJK.07/2020's declaration regarding the freedom of contract while choosing banking dispute resolution forums. Primary and secondary legal materials comprise most of the secondary data in this normative legal study. The information was gathered from the literature and examined using analytical and interpretive methods. The study's findings emphasised how Indonesian banking dispute resolution forums are chosen inconsistently with the idea of freedom of contract. The findings demonstrated the necessity of legal harmony in rulemaking to guarantee the coherence and consistency of all legal principles underlying different laws. This article argues that legal harmony is essential for aligning various legal concepts across diverse regulations and significantly contributes to the identification of the policy's inconsistency, which restricts the ability to choose a banking dispute settlement venue without restriction. The findings of this study may provide the basis for more research on how the policy affects banks and their clients. The findings could also be used as a reference for policymakers to improve the current policy and to ensure that the principle of freedom of contract is preserved in banking dispute resolution. Overall, this research provides valuable insights into the current policy and its impact on the banking industry in Indonesia.